Jonathan Belcher, Colonial governor - Batinski, Michael C., 1943- (The University Press of Kentucky, 2015)
As early as the eighteenth century, New England's ministers were decrying public morality. Evangelical leaders such as Jonathan Edwards called for rulers to become spiritual as well as political leaders who would renew the people's covenant with God. The prosperous merchant Jonathan Belcher (1682-1757) self-consciously strove to become such a leader, an American Nehemiah. As governor of three royal colonies and early patron of the College of New Jersey (later Princeton University), Belcher became an important but controversial figure in colonial America. In this first biography of the colonial.